(untitled) (Research, Society and Development, 2021)
Jelly is a type of candy that can be made with sour sugar and pectin. In order to use pepper and pineapple fruits, cultivated throughout the national territory, representatively in family farming, it is necessary to develop products that meet the needs of consumers. The objective of this work was to evaluate the quality and preference of goat pepper jelly (Capsicum chinenses L.) under different concentrations. For the manufacture of pepper jelly, the fruits were collected in the horticulture sector of the IF Goiano - Campus Ceres and went through the sanitization process in chlorinated water. After this process, pepper jelly with pineapple was manufactured. Physical-chemical and microbiological analyzes were performed in the instrumental and microbiological laboratory, checking the qualitative level and contamination of the jelly. Then, a sensory analysis was performed with 50 untrained tasters, in order to assess the acceptability index. The treatments were (T1-0.2, T2-0.4, T3-0.6, T4-0.8) grams of goat pepper in each jelly produced. Data were submitted to the Tukey test at 5% probability, in the UFSCar electronic spreadsheet. The evaluated samples presented the number of NMP≤ 3, being within the microbiological standards. The results of the physicochemical analyzes show that the jelly is within the standards of the literature. The sensory analysis showed an acceptability index higher than 70%, with values ​​between 80% and 90%. The treatments (T1-0.2; T4-0.8) with the lowest and highest concentration of peppers were the ones that had the best preference.